2019
DOI: 10.1111/vsu.13186
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between high‐field 3 Tesla MRI and computed tomography with and without arthrography for visualization of canine carpal ligaments: A cadaveric study

Abstract: Objective To compare the quality of visualization of canine carpal ligaments by using computed tomography (CT), MRI, CT arthrography (CTA), and magnetic resonance arthrography (MRA). Study design Prospective descriptive study. Study population Cadavers from dogs weighing more than 20 kg. Methods A 16‐slice CT scanner and a 3 Tesla MRI were used for the investigation. A dilute contrast medium was injected into the middle carpal and radiocarpal joints under fluoroscopic control, and CTA and MRA images were acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…In the present case, hyperextension was not present and was excluded clinically, whereas varus and valgus instability were detected. A previous study has indicated that advanced diagnostic imaging, including stress radiography, CT and MRI with or without arthrography, aids in determining the exact diagnosis and in better visualizing the injured structures 7 . In the present case, it was possible to detect moderate medial and mild lateral instability of the carpal joint and a slab fracture of the distal ulna with a combination of stress radiographs and CT images.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In the present case, hyperextension was not present and was excluded clinically, whereas varus and valgus instability were detected. A previous study has indicated that advanced diagnostic imaging, including stress radiography, CT and MRI with or without arthrography, aids in determining the exact diagnosis and in better visualizing the injured structures 7 . In the present case, it was possible to detect moderate medial and mild lateral instability of the carpal joint and a slab fracture of the distal ulna with a combination of stress radiographs and CT images.…”
Section: Discussionmentioning
confidence: 53%
“…A previous study Mild decalcification of the radial and ulnar styloid processes and carpal bones has indicated that advanced diagnostic imaging, including stress radiography, CT and MRI with or without arthrography, aids in determining the exact diagnosis and in better visualizing the injured structures. 7 In the present case, it was possible to detect moderate medial and mild lateral instability of the carpal joint and a slab fracture of the distal ulna with a combination of stress radiographs and CT images. The clinically and radiographically detected instability in combination with the non-reducible distal ulna necessitated surgery.…”
Section: Outcome and Follow-upmentioning
confidence: 66%
“…9 Additionally, the tendons of the ECR and the ECU could be followed until their insertion, which may be of clinical interest in the diagnosis of avulsion fractures 11 or enthesopathies. 17 Ligamentous injuries may lead to lameness, 4 bone luxation, 7 and carpal instability. Based on the authors' review of the literature the normal appearance of the dorsal ligaments -including the MCCL and LCCL -has only been reported using MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the authors' review of the literature the normal appearance of the dorsal ligaments -including the MCCL and LCCL -has only been reported using MRI. 4,5 A detailed guidance about their approach in the longitudinal plane was provided, which constitutes an advantage in comparison to MRI studies, since in this technique the oblique ligaments may not be entirely visible. Furthermore, in the in vivo phase of this study the scans were performed in slightly sedated or awake dogs with minimal physical restraint that represents another advantage in comparison with MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation